4-Membered Ring Carbocations: A Positive Development in the Synthesis of 3,3-Disubstituted Oxetanes and Azetidines - Juan J. Rojas; James A. Bull (CHIMIA, 2023)
4-Membered heterocycles are low molecular weight polar scaffolds with intriguing potential for drug discovery. Despite their unquestionable value, methods to access such heterocycles remain scant. Here, we describe the generation of oxetane- and azetidine- benzylic carbocations as a general strategy to access valuable 3,3-disubstituted derivatives.